2021
DOI: 10.1371/journal.pntd.0009408
|View full text |Cite
|
Sign up to set email alerts
|

The immune protection induced by a serine protease from the Trichinella spiralis adult against Trichinella spiralis infection in pigs

Abstract: Trichinellosis is a major foodborne parasitosis caused by Trichinella spiralis. In the present study, a serine protease gene from an adult T. spiralis (Ts-Adsp) cDNA library was cloned, expressed in Escherichia coli and purified by Ni-affinity chromatography. Previous studies of our laboratory have found that mice vaccinated with recombinant Ts-Adsp protein (rTs-Adsp) exhibited partial protection against T. spiralis infection. In this study, the protective effect of rTs-Adsp against T. spiralis infection in pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…SP from T. spiralis showed the immune protective effects on sodium dextran sulfate (DSS) induced colitis in C57BL/6 mice by reducing the severity of intestinal inflammation and disease index [24]. And SP induced the mix immune response of Th1/Th2 in pig and mice, exhibited partial protective effect on T. spiralis infection [25]. Moreover, Cystatin-like protein (CLP) and DNase II identified in Ts-ML-EVs could also induce protective immunity against T. spiralis in mice and pig respectively [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…SP from T. spiralis showed the immune protective effects on sodium dextran sulfate (DSS) induced colitis in C57BL/6 mice by reducing the severity of intestinal inflammation and disease index [24]. And SP induced the mix immune response of Th1/Th2 in pig and mice, exhibited partial protective effect on T. spiralis infection [25]. Moreover, Cystatin-like protein (CLP) and DNase II identified in Ts-ML-EVs could also induce protective immunity against T. spiralis in mice and pig respectively [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of vaccines may vary depending on animal species. Previous studies of our laboratory have found that immune response induced by the same antigen is different between pigs and mice ( Feng et al, 2013 ; Xu et al, 2021 ). Therefore, high levels of protection induced by candidate antigens in murine models should be further verified in swine models.…”
Section: Factors Of Vaccine Effectivenessmentioning
confidence: 84%
“…A previous study in our laboratory has found that mice vaccinated with recombinant T. spiralis serine protease (rTs-Adsp) exhibited a 46.5% reduction in muscle larvae ( Feng et al, 2013 ). Further research showed a 50.9% reduced worm burden of ML in pigs immunized with rTs-Adsp ( Xu et al, 2021 ). Furthermore, cysteine proteases of parasites are also a focus of attention for parasite vaccines.…”
Section: Vaccines Against T Spiralis Infectionmentioning
confidence: 96%
See 2 more Smart Citations